Species diversification and phylogenetically constrained symbiont switching generated high modularity in the lichen genus Peltigera. (27th May 2019) - Chagnon, Pierre‐Luc; Magain, Nicolas; Miadlikowska, Jolanta; Lutzoni, Francois
Abstract: Ecological interactions range from purely specialized to extremely generalized in nature. Recent research has showed very high levels of specialization in the cyanolichens involving Peltigera (mycobionts) and their Nostoc photosynthetic partners (cyanobionts). Yet, little is known about the mechanisms contributing to the establishment and maintenance of such high specialization levels. Here, we characterized interactions between Peltigera and Nostoc partners at a global scale, using more than one thousand thalli. We used tools from network theory, community phylogenetics and biogeographical history reconstruction to evaluate how these symbiotic interactions may have evolved. After splitting the interaction matrix into modules of preferentially interacting partners, we evaluated how module membership might have evolved along the mycobionts' phylogeny. We also teased apart the contributions of geographical overlap vs phylogeny in driving interaction establishment between Peltigera and Nostoc taxa. Module affiliation rarely evolves through the splitting of large ancestral modules. Instead, new modules appear to emerge independently, which is often associated with a fungal speciation event. We also found strong phylogenetic signal in these interactions, which suggests that partner switching is constrained by conserved traits. Therefore, it seems that a high rate of fungal diversification following a switch to a new cyanobiont can lead to the formation of large modules, with cyanobionts associating with multiple closely retated Peltigera species. Finally, when restricting our analyses to Peltigera sister species, the latter differed more through partner acquisition/loss than replacement (i.e., switching). This pattern vanishes as we look at sister species that have diverged longer ago. This suggests that fungal speciation may be accompanied by a stepwise process of (a) novel partner acquisition and (b) loss of the ancestral partner. This could explain the maintenance of high specialization levels in this symbiotic system where the transmission of the cyanobiont to the next generation is assumed to be predominantly horizontal. Synthesis. Overall, our study suggests that oscillation between generalization and ancestral partner loss may maintain high specialization within the lichen genus Peltigera, and that partner selection is not only driven by partners' geographical overlap, but also by their phylogenetically conserved traits. Abstract : Overall, our study suggests that oscillation between generalization and ancestral partner loss may maintain high specialization within the lichen genus Peltigera, and that partner selection is not only driven by partners' geographical overlap, but also by their phylogenetically conserved traits.